Ginsenosides on stem cells fate specification—a novel perspective - Liu, Ying; Jiang, Leilei; Song, Wenbo; Wang, Chenxi; Yu, Shiting; Qiao, Juhui; Wang, Xinran; Jin, Chenrong; Zhao, Daqing; Bai, Xueyuan; Zhang, Peiguang; Wang, Siming; et al. (Frontiers in Cell and Developmental Biology, 2023)
Recent studies have demonstrated that stem cells have attracted much attention due to their special abilities of proliferation, differentiation and self-renewal, and are of great significance in regenerative medicine and anti-aging research. Hence, finding natural medicines that intervene the fate specification of stem cells has become a priority. Ginsenosides, the key components of natural botanical ginseng, have been extensively studied for versatile effects, such as regulating stem cells function and resisting aging. This review aims to summarize recent progression regarding the impact of ginsenosides on the behavior of adult stem cells, particularly from the perspective of proliferation, differentiation and self-renewal.